Syafriadi Tando: Pemilik Usaha Kerupuk Kulit di Tandikek Barat Kecamatan Patamuan Kabupaten Padang Pariaman 1996-2023 - Gustia, Febi; Rusdi, Rusdi (Jurnal Kronologi, 2025)
This study examines the development of a traditional cracker (kerupuk kulit) business pioneered by Syafriadi Tando in Nagari Tandikek Barat, Padang Pariaman Regency, from 1996 to 2023. The research aims to describe how Syafriadi Tando’s family background and economic conditions shaped his character and entrepreneurial skills, the process of reviving the cracker business after it had been discontinued since 1980, as well as the strategies and challenges he faced in maintaining and expanding the business into a sustainable household enterprise despite limited capital and market competition. This study employs historical methods consisting of four stages: heuristics, source criticism, interpretation, and historiography. Data were collected through oral interviews with Syafriadi Tando and his family members, supported by personal documents, archives, and secondary sources such as books, journals, and articles related to traditional entrepreneurship. The findings reveal that the cracker business, originally established by Syafriadi’s father in 1967, had been halted for more than a decade before Syafriadi revived it in 1996 with a limited capital of IDR 250,000. Through perseverance, innovation, and family support, the business grew from serving local markets to reaching customers in other regions. Although it experienced a downturn between 2017 and 2018, Syafriadi successfully restored and expanded the business from 2020 to 2023. This case illustrates that perseverance, innovation, and a willingness to learn are key factors in building a sustainable business despite limited resources.